A Theory of Art - Berger, Karol -1947 (New York Oxford University Press, 2000)
What, if anything, has art to do with the rest of our lives, and in particular with those ethical and political issues that matter to us most? Will art created today be likely to play a role in our lives as profound as that of the best art of the past? A Theory of Art shifts the focus of aesthetics from the traditional debate of "what is art?" to the engaging question of "what is art for?" Skillfully describing the social and historical situation of art today, author Karol Berger argues that music exemplifies the current condition of art in a radical, acute, and revealing fashion. He also uniquely combines aesthetics with poetics and hermeneutics. Offering a careful synthesis of a wide breadth of scholarship from art history, musicology, literary studies, political philosophy, ethics, and metaphysics, and written in a clear, accessible style, this book will appeal to anyone with a serious interest in the arts.
Keywords: Esthetics